History and memory in the Chilean school. Contributions from Historical Thinking to teach difficult histories - González Calderón, Fabián (2024)
From a set of theoretical contributions elaborated by Dr. Peter Seixas in a limited time span (2000-2018), we propose to think and discuss about the teaching of history in Chile, in the context of the commemoration of the 50th anniversary of the civil-military coup of September 1973. Seixas’ work is used as a frame of reference focusing on the model of Historical Thinking and as a valuable experience of democratic and critical intellectuality. The Chilean case is presented in its essential curricular aspects and the ideas that emerge in the classroom are shown through three examples of narratives of the recent past elaborated by high school students. The conclusions take up classic works by Seixas to rethink both nationally and globally the challenges for history education in a new era characterized by the rise of dangerous extreme right-wing populisms.